A Comparative Investigation of Cutaneous Rabbit and Funneling Tactile Illusions for Implementation in Vibrotactile Displays. - Remache-Vinueza, Byron; Trujillo-León, Andrés; Vidal-Verdú, Fernando (IEEE, 2024)
We designed two psychophysical experiments to compare the cutaneous rabbit tactile illusion with a cutaneous rabbit recreated using sequential funneling tactile illusions. These illusions were rendered between a pair of actuators held with the hands. A tactile illusion is a psychophysical phenomenon that arises when the real stimulus does not match the perceived sensation. Designers exploit tactile illusions to efficiently increase the resolution of vibrotactile displays for human-computer interaction applications. Initially, participants qualitatively compared both rendering methods. Subsequently, individuals reported the upper threshold of the Inter-Stimulus Onset Interval (ISOI) for the cutaneous rabbit and the Time Between Funneling (TBF) illusions of the recreated cutaneous rabbit using funneling, when the illusion broke apart. The primary differences reported between both methods for rendering the cutaneous rabbit illusion were related to the perceived amount of jumps and duration. Overall, funneling performed better at evoking the illusion of a hopping rabbit, while both methods effectively conveyed direction sensations. Finally, the upper ISOI threshold we found for the cutaneous rabbit was consistent with the value reported in the literature, approximately 190 milliseconds, and was surpassed by the TBF of the recreated cutaneous rabbit using funneling.
Keywords: Tacto; Psicología fisiológica; Ingeniería biomédica; Cutaneous rabbit; Funneling; Haptic illusion; Haptic interface; Phantom sensation; Tactile illusion; Vibrotactile feedback; Vibrotactile interface